THE KOMBINASI RESISTANCE EXERCISE DAN STRETCHING LEBIH MENINGKATKAN KESEIMBANGAN STATIS DIBANDINGKAN STRETCHING PADA LANSIA DI DESA BLIMBINGSARI, KECAMATAN MELAYA, KABUPATEN JEMBRANA, BALI - Naibaho, Bagus; Wibawa, ari; Indrayani, Agung Wiwiek (Majalah Ilmiah Fisioterapi Indonesia; Vol 3 No 1 (2015): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2015.v03.i01.p04, 2015)
Age-related changes characterized by decrease of body function including the weakness of musculoskeletal system at lower extremities and disturbances of sensory system which affect human balance. The aim of this study was to investigate the combined effects of resistance exercise and stretching on static balance improvement among elderly. Experimental research has been performed with the design of pre-test and post-test group design. Samples were randomly assigned to an experimental (n=12) or control group (n=12). The experimental group performed stretching and resistance exercises, and the control group performed stretching exercises only. Static balance was measured before and after the 4-week intervention, the participants’ experimental and control group were evaluated using the One-Legged Stance Test (OLST). The result obtained p=0,000 (p<0,05) for experimental group with mean 5.58 ?1,50 and p=0,000 for control group with mean 4.00 ?1.47. The result means that in each group were significantly improved static balance. From the independent t-test obtained p=0,007 (p<0,05). It can be concluded that the combination of resistance exercise and stretching more effective to improve static balance compare with stretching.
Keywords: static balance, elderly, resistance exercise, stretching